Alterações dentoesqueléticas e do perfil facial em pacientes tratados ortodonticamente com extração de quatro primeiros pré-molares - de Oliveira, Giovani Fidelis; de Almeida, Marcio Rodrigues; de Almeida, Renato Rodrigues; Ramos, Adilson Luis [UNESP] (FapUNIFESP (SciELO), 2008)
Objective: the purpose of this prospective study was to cephalometrically analyze the dentoalveolar and soft tissue changes after the orthodontic treatment followed by the extraction of four premolars. Material and methods: the sample was comprised by 30 Class II division 1 patients with mean initial age of 12 years and 4 months. Two lateral cephalograms were obtained from each patient at the beginning and at the end of the treatment. The variables analyzed were the nasalabial changes and upper and lower incisors changes in relation to a vertical and horizontal x and y reference lines. Results: upper and lower incisors retraction was 3.4 and 1.8mm, respectively. The SNA angle was decresead by 1.7 degrees followed by a retraction of point A mainly due to the upper incisor retraction. There was a significant decrease of the Wits and ANB variables. There was an increase in the lower anterior facial height. Upper incisor retraction was followed by an increase in the nasolabial angle (ratio 1:2.8 degrees). However, a wide range of individual variability was found. Conclusions: the present study did not support the simple expectation that treatment with extractions of four premolars will result in a dished in face. It appeared that facial changes were more related to a normal facial growth, the amount of incisor retraction and the anchorage control during the upper and lower incisor.
Dentoskeletal and soft tissue profile changes after orthodontic treatment with first premolars extractions
Keywords: Facial profile; Orthodontic treatment; Pre-molars extractions